Microalgae Xanthophylls: From Biosynthesis Pathway and Production Techniques to Encapsulation Development - Slim Smaoui (MDPI AG, 2021)
In the last 20 years, xanthophylls from microalgae have gained increased scientific and industrial interests. This review highlights the essential issues that concern this class of high value compounds. Firstly, their chemical diversity as the producer microorganisms was detailed. Then, the use of conventional and innovative extraction techniques was discussed. Upgraded knowledge on the biosynthetic pathway of the main xanthophylls produced by photosynthetic microorganisms was reviewed in depth, providing new insightful ideas, clarifying the function of these active biomolecules. In addition, the recent advances in encapsulation techniques of astaxanthin and fucoxanthin, such as spray and freeze drying, gelation, emulsification and coacervation were updated. Providing information about these topics and their applications and advances could be a help to students and young researchers who are interested in chemical and metabolic engineering, chemistry and natural products communities to approach the complex thematic of xanthophylls.